2011
DOI: 10.12659/msm.881770
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Patella Baja after total knee arthroplasty

Abstract: SummaryBackgroundOne of the complications of total knee arthroplasty (TKA) which has not yet been directly addressed is pseudo-patella baja (PPB). True patella baja (PB) is present when the length of the patellar tendon becomes shorter. PPB is present when the patella tendon is not shortened, but the level of the joint line is elevated. This study was conducted to assess PPB in TKA.Material/MethodsSixty patients who had had a primary TKA at our center between 1995 and 2005 were included. The average follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 16 publications
1
48
3
5
Order By: Relevance
“…In addition, we found that cartilage stress plateaued when patella height had been corrected close to normal (InsallSalvati ratio approximately 1.0); further distalization did not provide lower values. Clinically, a low-lying patella or elevated tibiofemoral joint line also may lead to several complications such as joint stiffness, decreased ROM, and anterior knee pain [11,14,28]. Therefore, we advocate proper distalization of the tibial tubercle to correct the Insall-Salvati ratio to normal.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that cartilage stress plateaued when patella height had been corrected close to normal (InsallSalvati ratio approximately 1.0); further distalization did not provide lower values. Clinically, a low-lying patella or elevated tibiofemoral joint line also may lead to several complications such as joint stiffness, decreased ROM, and anterior knee pain [11,14,28]. Therefore, we advocate proper distalization of the tibial tubercle to correct the Insall-Salvati ratio to normal.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have suggested that patellar baja increases the risk of patellar fracture. [34][35][36] Although the position and resection angle of the patellar component were not found to be a significant risk, patellar over resection and increased delta patellar tilting angle did increase the incidence of patellar fracture. These factors probably compromise the mechanical strength of the patella.…”
Section: Discussionmentioning
confidence: 85%
“…19,20 Kazemi et al study done in 2010, on 60 patients (with prior patella baja patient exclusion) shows 43 had no joint line elevation or patellar tendon shortening. 21 Divided patients into 3 groups-Group A had no patella baja or pseudo-patella baja, Group B had pseudo-patella baja and Group C had patella baja and pseudo-patella baja patients. 15 patients demonstrated joint line elevation, and both patella baja and pseudo-patella baja were present in 2 patients.…”
Section: Resultsmentioning
confidence: 99%
“…About 25 to 30% of TKRs may develop patella infera. 7 The current study was designed so as to assess whether jointline elevation and change in patellar tendon length influences knee flexion after primary cruciate retaining TKR.…”
Section: Introductionmentioning
confidence: 99%